“This seems important”: A thematic analysis of reflections on a compulsory induction program for new Malaysian university teachers - Daron Benjamin Loo; Farous Izwan Bin Abdul Aziz; Nadiah Rus Liyana Binti Rusli; Yong Zi Hong (Universiti Pendidikan Sultan Idris, 2024)
The aim of this study is to examine information perceived as salient by new university academic staff attending a compulsory induction program at a Malaysian public university. Attending and successfully completing the induction program is a policy that is set and managed by universities across Malaysia. This study uses a qualitative approach, where reflections by the four authors of this study attending a ten-day induction program were collected and examined. By the end of the program, a total of 40 reflective pieces were written on an online shared document, which were then analyzed thematically. The reflections were examined through iterative reading and coding of their contents, which were then consolidated into salient themes. These themes were noteworthy information, affirmation and aspiration, and critical response. The findings indicated that the process of induction acted more than just a space for the dissemination of information, but there were instances where participants found acknowledgement through an alignment of beliefs, as well as developing criticality towards issues emergent from the topics covered during the induction program. Moreover, the compulsory induction program was in itself a gateway for new university teachers to become aware of other university policies that may affect their work in the Malaysian higher education context.